THE EFFECT OF AEROBIC CIRCUIT TRAINING METHOD ON INCREASING AGILITY - Amtsal Firdaus; Idris Supriadi (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2025)
Indonesia has participated in the Olympics since 1952 and until 2020 collected 37 medals, but this achievement is still not optimal so that evaluation and strengthening of the national sports development system are needed (Kemenpora, 2021). The problem that occurs is the scheduling of competitions that are not timely. The purpose of this study was to determine how agility is improved after being given an aerobic circuit training program. The research method used was a One Group Pretest-Posttest Design by giving treatment to 10 PJKR 2022 students of STKIP Syekh Manshur. The results showed that Aerobic Circuit Training had a significant effect on increasing agility, the pre-test obtained an average of 11.9520 and after being given Aerobic Circuit Training treatment, the average post-test result was 7.6620. The results of the hypothesis test showed a significance value of 0.000 <0.05, so H0 was rejected. It can be concluded that there is an effect of aerobic circuit training on improving agility abilities.